PENGEMBANGAN KAPASITAS MASYARAKAT DI DESA TUMALUNTUNG KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA MELALUI BADAN USAHA MILIK DESA - LUMEMPOUW, SALLY; RURU, JOORIE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2021)
The development of community capacity in Tumaluntung village through the Village Owned Enterprises Institution (BUMDes), it seems that there are still indications of problems. such as the lack of public awareness in managing the funds they get from BUMDes and the lack of guidance or training from the BUMDes Institution for people who use the BUMDes program, so there is no visible change in Community Capacity Development in Tumaluntung Village. This study uses a qualitative approach. Data obtained from interviews, observations and documents. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings of this study are that the development of community capacity in Tumaluntung Village through the existing BUMDes from the aspect of human resources related to: the dimensions of knowledge and skills as well as motivation. The management of the Village-Owned Enterprises Institution in the village of Tumaluntung should pay more attention to the community using BUMDes and also people who do not use BUMDes, and create programs to motivate the community to create Community Capacity Development, as well as create programs to provide training to the community. in order to increase the knowledge and skills of the community. Kay Word : Capacity Building, Village Owned Enterprises